Pengaruh Disiplin Kerja Terhadap Produktivitas Pegawai (suatu studi di Kantor Kelurahan Tingkulu Kecamatan Wanea Kota Manado) - Ruauw, Astria; Lengkong, florence Daicy; Mandey, Jantje (JURNAL ADMINISTRASI PUBLIK, 2015)
ABSTRACT Labor discipline is a behavioral containing technical aspects that work ethic is the normsthat are binding and are set explicitly and practices such as behavioral attitudes respect, honor, obey, andobey that must be held to be maintained and implemented in government agencies. Problems to beanswered in this study is the work discipline of employees about employee performance affects theproductivity of employees working in the Village Tingkulu Wanea districts of Manado. This study aims todetermine the effect of labor discipline against the employee productivity. These results indicate that thelabor discipline and significant positive effect on the productivity of employees in the Village TingkuluWanea District of Manado City. Based on these conclusions labor discipline must be observed andmaintained on each employee so that the tasks and responsibilities can be a priority terselenggarakan well.Keywords: influence, discipline, performance, employee productivity